2018
DOI: 10.5152/tud.2018.88615
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stone-free status after single-session retrograde intrarenal surgery for renal stones

Abstract: Stone volume could be a more reliable parameter than stone size in predicting RIRS success. Lower pole stone location and UAS use could be considered the most significant predictors of SFS after single session RIRS for single renal stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…likely to have residual stones after fURS compared to patients having stones at other locations (35). Evidently, the spontaneous passing of stone fragments after the surgery was more difficult due to the position of the lower pole.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…likely to have residual stones after fURS compared to patients having stones at other locations (35). Evidently, the spontaneous passing of stone fragments after the surgery was more difficult due to the position of the lower pole.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to middle and upper pole stones, the fURS treatment of lower pole stones is more complicated because of the anatomical factors and the limited deflection angle of flexible ureteroscopes ( 34 ). Additionally, Tonyali et al reported that patients with lower pole stones are 2.25 times more likely to have residual stones after fURS compared to patients having stones at other locations ( 35 ). Evidently, the spontaneous passing of stone fragments after the surgery was more difficult due to the position of the lower pole.…”
Section: Discussionmentioning
confidence: 99%
“…The R.I.R.S scoring system consisted of stone density, stone in the lower pole with infundibulopelvic angle < 30 o , infundibulum length, and stone burden 9 . One study by Tonyali et al proposed that the lower pole stone location and the use of a ureteral access sheath were significant factors 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated factors that predict stone‐free and surgical success. In some studies, stone size, presence of lower pole calculi, surgical experience, presence of hydronephrosis, and UAS use are significant predictors of RIRS outcomes, while others have only found the number of stones and the number of sites to be significant 17‐19 . Particularly because of the advances in the field of lasers, stone access is the most important factor in making treatment possible.…”
Section: Discussionmentioning
confidence: 99%